Optimization strategy for sound environment of college basketball stadium - Jinyu Liang (PLoS ONE, 2025)
As an important sports venue, the sound environment of the basketball stadium is crucial for the experience of spectators and participants. In order to improve the quality of the acoustic environment of the basketball stadium, the acoustic parameters such as reverberation time, language transmission index and background noise were used to build a comprehensive evaluation system, and the software simulation was improved and optimized. The results show that the language transmission index of most measuring points in the basketball stadium has a high consistency between the on-site measurement values and the simulation results, and the simulation results are relatively accurate. The improved language transmission index values of each measurement point have significantly increased, with an average of 0.58, an increase of 93.33% compared to before the improvement. The improvement strategy effectively improves the acoustic environment of the basketball stadium and better controls the reverberation time in the stadium. The research provides a valuable analysis of the optimization of the sound environment of college basketball stadiums, which provides some reference for the improvement of the sound environment of basketball stadiums, and also has some reference significance for the optimization of the sound environment of other sports venues or entertainment venues. Index terms college basketball stadium; acoustic environment; optimization strategy; acoustic simulation; AHP.